Penerapan Kegel Exercise terhadap Penyembuhan Luka Perineum pada Ibu Post Partum - Fahrur Cindy Nur Aini; Anjar Nurrohmah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Background: Post partum is a condition where the reproductive organs are restored to their pre-pregnancy state. The process of childbirth almost 90% experience perineal tears. To be able to accelerate perineal wounds can be with pharmacological and non-pharmacological measures, one of which is non-pharmacological action with kegel exercise, kegel exercise is pelvic muscle training by contracting the muscles. Objective: to describe the results of observations of wound healing and changes in wound characteristics in post partum women. Methods: This research is a case study research using descriptive methods, namely by observing 2 (two) respondents of post partum women with perineal rupture. Performed for 7 days of application and wound evaluation on day 8. Results: This application shows that before Kegel exercise was performed, both respondents' perineal wound conditions were classified as moderate wounds, namely wet wounds, perineal closure, no signs of infection. After evaluation on the eighth day, the wound condition of Mrs. D and Mrs. E was classified as a good wound, namely dry perineal wounds closing and no signs of infection. Conclusion: There are differences in wound healing and changes in perineal wound characteristics in postpartum women.